PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN JASA KERETA API STASIUN TAWANG DI KOTA SEMARANG - Sri Maryati, 10.05.51.0048 (Students Journal of Economic and Management, 2014)
This study aimed to examine the level of customer satisfaction and loyalty by examining variables that influence satisfaction and loyalty identified passenger services Semarang Tawang Railway Station, in this study defined variables expected to affect customer loyalty, which is the variable quality of service and customer satisfaction. A sample of respondents in this study were 100 respondents. Sampling method using purposive sampling using sample criteria were respondents who use the services of Semarang Tawang Railway Station at least twice and at least the age of more than 10 years. The collected data were analyzed using factor analysis to test the validity of the question items, and the Cronbach alpha to test the reliability of the instrument. Analysis of the data used in this study is the use of SPSS for Windows 16.0, which is used to test four hypotheses that have been developed.The results of the analysis of data that have been in if the show a positive and significant relationship between service quality and customer satisfaction to customer loyalty. From the test results of the mediation service quality can directly influence customer loyalty through customer satisfaction without. So it can be concluded to build customer loyalty takes them quality service and customer satisfaction.Keywords: Quality of Service, Customer Satisfaction and Customer Loyalty.